Perkembangan Gugatan Perbuatan Melanggar Hukum oleh Pemerintah Pasca-Undang-Undang Nomor 30 Tahun 2014 (Development of Lawsuit for Law Violation by the Government Post Statute/Law Number 30 of 2014) - Bagus Oktafian Abrianto; Xavier Nugraha; Nathanael Grady (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2020)
The existence of a lawsuit for unlawful acts by the authorities (onrechtmatige overheidsdaad) is one of the means of providing legal protection for the citizens from actions (handling) carried out by the government. Over time, the concept of onrechtmatige overheidsdaad has develops dynamically. The change in the concept of the State Administrative Decree in Article 87 of Law Number 30 of 2014 concerning Government Administration has caused an onrechtmatige overheidsdaad lawsuit which was once the absolute competence of the District Court, and now became the absolute competence of the State Administrative Court. This research attempts to explain the changes in the regulation and changes in the concept of onrechtmatige overheidsdaad after the enactment of Law Number 30 of 2014. The transfer of authority to examine onrechtmatige overheidsdaad lawsuit from the general court to the state administrative court has various juridical consequences, ranging from changes in procedural law, petitum and posita. One of the important consequences is a change related to the implementation or execution of the judicial decision, where in the past, when an onrechtmatige overheidsdaad lawsuit was an absolute competence of a district court, the implementation of the decision depended on the good will of the government. However, after becoming absolute competence of the Administrative Court, there is a mechanism of forced efforts so that the decision can be carried out by the relevant government agencies (defendants).AbstrakKeberadaan gugatan perbuatan melanggar hukum oleh penguasa (onrechtmatige overheidsdaad) merupakan salah satu sarana pelindungan hukum masyarakat atas tindakan (handeling) yang dilakukan oleh pemerintah. Adapun konsep mengenai onrechtmatige overheidsdaad berkembang secara dinamis dari waktu ke waktu. Perubahan konsep Keputusan Tata Usaha Negara (KTUN) di dalam Pasal 87 Undang-Undang Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan, menyebabkan gugatan onrechtmatige overheidsdaad yang dahulu merupakan kompetensi absolut Pengadilan Negeri, berubah menjadi kompetensi absolut Pengadilan Tata Usaha Negara. Penelitian ini berusaha memaparkan mengenai perubahan pengaturan dan perubahan konsep onrechtmatige overheidsdaad pasca berlakunya Undang-Undang Nomor 30 Tahun 2014. Beralihnya kewenangan untuk memeriksa gugatan onrechtmatige overheidsdaad dari lingkungan peradilan umum ke peradilan tata usaha negara memiliki berbagai konsekuensi yuridis, mulai dari perubahan hukum acara, petitum, dan posita. Salah satu konsekuensi yang cukup penting adalah perubahan terkait dengan pelaksanaan putusan atau eksekusi. Dahulu, gugatan onrechtmatige overheidsdaad merupakan kompetensi absolut pengadilan negeri, sehingga pelaksanaan putusan tergantung dari itikad baik (good will) dari pemerintah. Pasca-beralih ke kompetensi absolut PTUN, terdapat mekanisme upaya paksa agar putusan tersebut dapat dijalankan oleh instransi pemerintah terkait (tergugat).